Gakkel Ridge plagioclase and olivine mineral and melt inclusion analyses (IEDA: EarthChem Library)
The depth of crystallisation within mid-ocean ridge magma plumbing systems can be constrained using the volatile content of melt inclusions. Here the volatile-, trace- and major-element compositions of both olivine- and plagioclase-hosted melt inclusions from the Gakkel Ridge (Arctic Ocean) are presented. Host mineral major elements are also presented and were used to undertake melt inclusion post-entrapment crystallisation corrections.